Effect of weaning age on morphological and histological changes that occur in a rat's testis - Yonatan Crispel; Yonatan Danin; Geula Klorin; Ze'ev Hochberg (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
Background: Weaning of mammalian progeny is associated with a change in body shape and physical characteristics. It programs growth, body composition, and the tempo of physiological development and maturation, as well as litter size and parity and, thereby, reproductive strategy.  Methods: To evaluate the effects of weaning age on morphological and histological changes that occur in a rats' testis, we assessed testis size weekly and histomorphometry in 30 days old pups, and 90 days old mature rats that had been weaned early (d16), normally (d21), or late (d26).  Results: Early weaning resulted in large testes at age 30 days and beyond, a wide seminiferous tubule wall, and the ratio of blood vessel to the stroma was bigger than in late weaned animals. At age 90 days, and the next generation the litter size of early-weaned rats was bigger than those weaned on days 26 or 21.  Conclusions: Early weaning significantly enhances the testes' size, vasculature, and seminiferous tubular walls, and enhances the liter size compared to late weaning.